Effectiveness sapindus saponaria on the control of boophilus microplus ticks in cattle (Revista Electrónica REDINE, 2017)
A study was carried out with the objective of evaluating the effectiveness of the aqueous extract of the fruit of Jaboncillo (Sapindus saponaria) in the control of the tick Boophilus microplus in cattle. For the in vitro study, 128 adults were used, which were distributed in three experimental groups and one control group treated with Ivermectin. The experimental groups were treated with aqueous extract of Jaboncillo at concentrations 256, 512 and 1024 ppm. The results show that there is no significant difference between the effect of Ivermectin and the treatment 256 ppm, however the treatments 512 ppm and 1024 ppm produce the same effect in the control of ticks with death values of 0.800 and 0.730 respectively. Later in the in vivo phase it was demonstrated that there was no alteration in the health status of the treated animals, a positive effect on the skin, improving its appearance and the rate of infestation decreased from 65 to 9. It was concluded that the Jaboncillo tree (Sapindus saponaria) has a high acaricidal potential when used in dual-purpose cattle.
Keywords: soap (Sapindus saponaria); tick (Boophilus microplus); aqueous extract